Predictive factors for anti-HBs status after 1 booster dose of hepatitis B vaccine. Issue 39 (September 2016) - Lu, I-Cheng; Jean, Mei-Chu Yen; Lin, Chi-Wei; Chen, Wei-Hung; Perng, Daw-Shyong; Lin, Chih-Wen; Chuang, Hung-Yi
Abstract : Abstract: In Taiwan, infants need to receive 3 doses of hepatitis B virus (HBV) vaccine under the public health policy from the government. However, there are many young adults who even though received complete HBV vaccination in their childhood would lose the positive response of anti-hepatitis B surface antibody (HBs) and need the booster dose of HBV vaccine. The aim of our study is to determine the powerful predictive factor for screening the candidates who need only 1 booster dose of HB vaccine then they can regain positive postbooster anti-HBs status (≧10 mIU/mL) or protective postbooster anti-HBs status (≧100 mIU/mL). We recruited 103 university freshmen who were born after July 1986 with complete HBV vaccination in childhood, but displayed negative results for hepatitis B surface antigen and anti-HBs levels at their health examinations upon university entry. They received 1 booster dose of HB vaccine, and their anti-HBs titers were rechecked 4 weeks after the booster administration. Multivariate analysis logistic regression for positive postbooster anti-HBs status (≧10 mIU/mL, model 1) and protective postbooster anti-HBs status (≧100 mIU/mL, model 2) was done with predictive factors of prebooster anti-HBs level, body mass index, serum glutamate pyruvate transaminase level, and sex. Twenty-four students got positive postbooster anti-HBs status (10–100 mIU/mL) and 50 students got protective postbooster anti-HBs status (≧100 mIU/mL). In the model of multivariate analysis logistic regression for positive postbooster anti-HBs status (≧10 mIU/mL), prebooster anti-HBs level was the strongest predictive factor. The odds ratio was 218.645 and the P value was 0.001. Even in the model of multivariate analysis logistic regression for protective postbooster anti-HBs status (≧100 mIU/mL), prebooster anti-HBs level was still the strongest predictive factor, but the odds ratio of a protective booster effect was 2.143, with 95% confidence interval between 1.552 and 2.959, and the P value was less than 0.001. Prebooster anti-HBs level can be the powerful predictive factor for positive postbooster anti-HBs status (≧10 mIU/mL) and protective postbooster anti-HBs status (≧100 mIU/mL). According to the result of this study, if someone received complete HBV vaccination in childhood, but displayed negative results for hepatitis B surface antigen and anti-HBs levels around 2 decades later, 1 booster dose of HBV vaccine could help him or her to regain positive postbooster anti-HBs status (≧10 mIU/mL) under the strong predictive factor of prebooster anti-HBs level higher than 1 mIU/mL. The other 2 HBV vaccines could be saved and the case could also save money and time.